Inhibitory effects of an aqueous extract from Cortex Phellodendri on the growth and replication of broad-spectrum of viruses in vitro and in vivo. Issue 1 (December 2016) - Kim, Jae-Hoon; Weeratunga, Prasanna; Kim, Myun Soo; Nikapitiya, Chamilani; Lee, Byeong-Hoon; Uddin, Md Bashir; Kim, Tae-Hwan; Yoon, Ji-Eun; Park, Chung; Ma, Jin Yeul; Kim, Hongik; Lee, Jong-Soo
Abstract Background Cortex Phellodendri (C. Phellodendri), the dried trunk bark ofPhellodendron amurense Ruprecht, has been known as a traditional herbal medicine, showing several bioactivities. However, antiviral activity of C. Phellodendri aqueous extract (CP) not reported in detail, particularly aiming the prophylactic effectiveness. Methods In vitro CP antiviral activity evaluated against Influenza A virus (PR8), Vesicular Stomatitis Virus (VSV), Newcastle Disease Virus (NDV), Herpes Simplex Virus (HSV), Coxsackie Virus (H3-GFP) and Enterovirus-71 (EV-71) infection on immune (RAW264.7) and epithelial (HEK293T/HeLa) cells. Such antiviral effects were explained by the induction of antiviral state which was determined by phosphorylation of signal molecules, secretion of IFNs and cytokines, and cellular antiviral mRNA expression. Furthermore, Compounds present in the aqueous fractions confirmed by HPLC analysis and evaluated their anti-viral activities. Additionally, in vivo protective effect of CP against divergent influenza A subtypes was determined in a BALB/c mouse infection model. Results An effective dose of CP significantly reduced the virus replication both in immune and epithelial cells. Mechanically, CP induced mRNA expression of anti-viral genes and cytokine secretion in both RAW264.7 and HEK293T cells. Furthermore, the main compound identified was berberine, and shows promising antiviral properties similar to CP. Finally, BALB/c mice treated with CP displayed higher protection levels against lethal doses of highly pathogenic influenza A subtypes (H1N1, H5N2, H7N3 and H9N2). Conclusion CP including berberine play an immunomodulatory role with broad spectrum antiviral activity, due to induction of antiviral state via type I IFN stimulation mechanism. Consequently, C. Phellodendri could be a potential source for promising natural antivirals or to design other antiviral agents for animal and humans.